Transition from e-Government to m-Government: Challenges and Opportunities - Case Study of UAE - Alharmoodi, Badir Yousif Rafee; Muhammad Modi B. Lakulu (European Journal of Multidisciplinary Studies, 2020)
This study aims to explore the challenges of the transition from e-government to m-government as well as to identify and develop a workable framework on m-government standards, protocols and its inherent opportunities for various business engagements. The objectives of the study are to identify strategic challenges in various government organizations that impede transition from e-government services to m-government services, formulate a framework of m-government for government and private business organizations to tackle the challenges and enhance the opportunities using Fuzzy Delphi method, and to validate the proposed framework using Fuzzy Delphi method. A survey questionnaire is used to gather data on the study constructs. The validation of formulated framework is based on Fuzzy Delphi method. Descriptive statistics is used to determine the frequency of the demographical variables. Independent sample T-test is used to test the hypothesis in other to show the variance in the constructs against the dependent variable. This study has identified through systematic literature review five (5) categories of challenges and opportunities.